ROMANO-WARD SYNDROME ASSOCIATED WITH TU ELECTRICAL ALTERNANS - DJAWAN; S; SHAFAYAN; B (Acta Medica Iranica, 1981)
A case o f the electrical alternans of t he TU wave and peri odic nega t ive U wave associated with c l ini cal symptoms , e lectrocardi ographic a nd postmortem findi ng s o f Romano- Ward Syndrome has been pres ented. No e lec ~ r o l y te d ist urbance was found t o be r esponsible for t his exceptional l y rare situation . Changes i n A-V conduct i on and left bu n• d Ie branch block could be a t tributed to the d i f f use c or onary s clero sis and s ubs equent i schemia in the myocardial c onduction t.issues . The e lectrical alternans of t he U wave or TU complex of the e lectrocardiogram i s an exceeding ly r are s i t uation without any clearly known mechanism for i ts appea rance . A case of thi s phenome no~ i n as soc iation with RomanoWard Syndrome has been presented whe rein an abnorma l ity i n A-V conduction and left bund le branch block cou ld be encountered .